Principles of Marketing - Philip Kotler (Pearson Education Limited, 2016)
For undergraduate Principles of Marketing courses Today's marketing challenge is creating vibrant, interactive communities of consumers who make products and brands a part of their daily lives. Learn how to create value and gain loyal customers. Kotler/Armstrong is a comprehensive, classic principles text organized around an innovative customer-value framework. Students learn how to create customer value, target the correct market, and build customer relationships. The changing nature of consumer expectations means that marketers must learn how to build communities in addition to brand loyalty.